THE EFFECTIVENESS OF SCAFFOLDED READING EXPERIENCE IN TEACHING READING VIEWED FROM STUDENTS’ INTELLIGENCE - Aksendro Maximilian (Bandar Lampung University (UBL), 2016)
Reading the English text has always been a nightmare for most vocational school students. However, having good ability in comprehending English text is a must for them since many instuctions which must be read by students are written in English. This research deals with scaffolded reading experience (SRE) as an alternative way in teaching English reading. SRE is a set of pre-reading, during-reading, and post-reading activities which is specifically designed to assist the students in successfully reading, understanding, and enjoying the English text. The objectives of this research are: (1) to identify whether SRE is effective to teach reading; (2) to identify whether students who have high intelligence have better reading ability than those who have low intelligence; and (3) to identify whether there is an interaction effect between teaching methods and students’ intelligence on the students’ reading ability. This is an experimental research which is conducted at SMK PGRI 2 Bandar Lampung. The researcher analyzes the data using ANOVA and Tukey test. Based on the result of data analysis, the research findings are: (1) SRE is effective to teach reading; (2) the students who have high intelligence have better reading ability than the students who have low intelligence; and (3) there is an interaction effect between teaching methods and students’ intelligence on the students’ reading ability. The research result of this study implies that SRE is effective in teaching reading viewed from students’ intelligence. From that result, ideally, scaffolded reading experience could be implemented in the classroom in order to achieve optimal result.